Dominant Understorey Plants Producing Herbal Medicine Materials on Homegarden Agroforestry System in Menoreh Hills, Kulon Progo District - Widyastuti, S.M.; Hadi, Etik Erna Wati; Wahyuono, Subagus (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Priority products in homegarden agroforestry systems are still dominated by wood. Understorey is an important component of the homegarden community, but not a priority in its management because there is not much information about its benefits. Undestorey has several benefits such as food sources, food crops and medicinal materials. Research aimed to know the diversities of understorey species, the dominant of understorey species and the content of compounds in dominant understorey in the homegarden agroforestry system in Menoreh hill, Kulon Progo Regency. The study sites were categorized into 3 zones based on elevation, i.e. zone 1 (< 300 m above sea level (asl)), zone 2 (301-600 m asl) and zone 3 (> 600 m asl). This research method used inventory and identification of understorey species, and identification the content of dominant understorey compound by TLC method. The results showed that there were 41 species of understorey, the dominant species in zones 1, 2 and 3 were Curcuma mangga Val. Zone 3 produced the highest diversity. Based on the similarity index, there was a difference between the homegarden groups in zones 1, 2 and 3. Phenols and terpenoids were identified as in C.mangga.